Oral findings and clinical implications of patients with congenital neutropenia: a literature review - Tirali, R. Ebru; Yalçınkaya Erdemci, Zeynep; Çehreli, S. Burçak (The Turkish Journal of Pediatrics, 2013)
Neutropenia is a granulocyte disorder characterized by a dramatically low number of neutrophils, the most important type of white blood cell. The condition results in susceptibility to severe pyogenic infections. Some people are born with it (congenital neutropenia), and others develop it as young children. The disease is so-called chronic neutropenia when lasting more than two months. This article reviews the definition, clinical properties and common oral manifestations of congenital neutropenia in order to highlight the importance of diagnosis, oral hygiene maintenance and dental treatments.